MitigatePlus: Research for low-emission food systems - Verchot, Louis V.; Zhang, Wei (International Food Policy Research Institute, 2022)
Mitigate+ Research for Low-Emission Food Systems is one of the Research Initiatives in CGIAR’s new research portfolio that will deliver science and innovation to transform food, land, and water systems in a climate crisis. Mitigate+ focuses on reducing greenhouse gas emissions from food systems and the predicted consequences of climate change on sustainable development and social equity. The initiative expects to help countries reduce emissions by 1.1 gigatons (6.5%) by 2030. An estimated 8 million people will benefit from these reduced emissions and from the associated co-benefits over the Initiative’s ten-year lifespan.